Azeredo Coutinho : refutação "das Luzes" em defesa da instituição escravista no Brasil colônia - Silva, Débora de Liz e (2009)
Azeredo J. J. of Cunha Coutinho, in the philosophical historical context referring to the centuries XVIII and XIX, writes relevant works for understanding of the questions of the centuries "of the Lights". The central axle of his works prioritizes the economical strengthening of the Metropolis Portugal and its colony Brazil. For such, the Brazilian thinker builds economical theories, proposes scientifie inquiries, improvement of the agricultural techniques, theories of civilization, production of excesses, commerce and industries. However, to defend his theories centered in the economical strengthening and wealth of the Metropolis and colonial Brazil it is necessary to refute the philosophical speeches of sects and revolutionary sources that intellectuals inflame with his ideas of equality, natural rights and social pact, speeches that culminated in antislavish ideas. Azeredo, in the work Analysis, defends explicitly the slavish institution and while defending it cause nuisance in his contemporaries, Brazilian liberais and Brazilian historiography.